Effect of niacin on blood metabolities, rumen protozoa, insulin levels and fatty liver in experimentally induced ketosis in ewes - Veysi Aslan; Reşat Aştı; Ali Muhtar Tiftik; Mürsayettin Eksen (Eurasian Journal of Veterinary Sciences)
In this investigation, phlorizin was used to induce ketosis in Akkaraman ewes. Before the experiment, all ewes were examined clinically. After the blood was obtained from jugular vein and SGO T, serum insulin levels, blood sugar and total protein concentrations, Na, K levels, Hb and PCV, total leucocyte and differential leucocyte separations were counted. These parameters were accepted as a normal values, phlorizin was injected twice daily to each anim.al for a period of 12 days. Clinical and blood examinations ofewes were controlled on the lit, 3th, 6th, 9th days after injection of phlorizin. At the end of phlorizin injection to sheep, rumen content and liver biopsi materials were obtained. Normal SGO T, serum insulin, blood sugar, total protein concentrations, Na, K levels, Hb and PCV, total leucocyte count were found to be as 48.2 UJ L, 22.53 mIU\ ml, 65.1 mg\dl, 5.86 / dl, 138.4 mEq/L, 16 mEq/L, 6.08 % mg, 28 %, 10.6 X 101 respectively. These parameters have been changed at the end of phlorizin injection (on the 12 day) as 105.72 U/ L, 4.52 mIU\ ml, 32.3 mg) dl, 6.6 gr\ dl, 315.8 mEqjL, 17 mEq/L, 5.24 % mg, 28 %, 13.9 X 103 respectively and total rumen protozoa count decreased to 20.200 + 4852 / ml and diffuse lipit infiltrastion was seen in epithelial cells of liver.